ARTI PENTING EVALUASI POLITIK FORMULASI KEBIJAKAN PUBLIK BAGI KELANGSUNGAN PEMERINTAHAN - Gedeona, Hendrikus Triwibawanto (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
Is the performance of government good or substandard? Can government resoluteness be maintained? Public policy becomes one of the indicators to asses government performance because, through public policy, citizens can appraise the government?s vision, mission, goal, and objectives. However, in practice, a lot of cases show that the government?s policies have not met the citizen?s expectations, interests and needs. One of the causes is estimated to roof from the government or policy makers negligence toward the political evaluation of public policy formulation. What does political evaluation mean? How is the political evaluation interrelated with government resoluteness? The writer will discuss the issues in this article.